2008
DOI: 10.1007/s00442-008-1177-9
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization leads to host-use divergence in a polyphagous butterfly sibling species pair

Abstract: Climate warming has lead to increased genetic introgression across a narrow hybrid zone separating the eastern and Canadian tiger swallowtails (Papilio glaucus and Papilio canadensis). This situation has led to the formation of an allochronically separated hybrid population with a delayed emerging phenotype or "late flight". Here, we assess how the recombination of the parental genomes that lead to this phenotype may have facilitated another major ecological shift, host-use divergence. We first contrast the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 69 publications
0
54
0
Order By: Relevance
“…Together, these data show that its history of introgression is dissimilar to appalachiensis . The late flight has the potential to speciate through allochronic flight period and larval host plant specialization [20], [41]; however, unlike appalachiensis , it may be a transient phase in the northward movement of the glaucus-canadensis hybrid zone in a changing thermal landscape. Moreover, although selection may maintain some characteristics of a mosaic sex chromosome in the late flight [20], [37], our data suggest that the late flight may not be experiencing natural selection for the same sex chromosome mosaicism that seems to have been essential in generating and maintaining the hybrid phenotype of appalachiensis .…”
Section: Resultsmentioning
confidence: 99%
“…Together, these data show that its history of introgression is dissimilar to appalachiensis . The late flight has the potential to speciate through allochronic flight period and larval host plant specialization [20], [41]; however, unlike appalachiensis , it may be a transient phase in the northward movement of the glaucus-canadensis hybrid zone in a changing thermal landscape. Moreover, although selection may maintain some characteristics of a mosaic sex chromosome in the late flight [20], [37], our data suggest that the late flight may not be experiencing natural selection for the same sex chromosome mosaicism that seems to have been essential in generating and maintaining the hybrid phenotype of appalachiensis .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Z-linked species diagnostic traits [allozymes ( Fig. 1; Scriber and Ording 2005); diapause (Rockey et al 1987;Scriber and Ording 2005); ovipositional behavior Mercader et al 2009)] and autosomal species diagnostic traits [wing morphology (Table 1; Scriber and Ording 2005); larval detoxiWcation abilities (Scriber and Ording 2005;Mercader et al 2009)] have indicated a signiWcantly greater number of hybrid characteristics in the late Xight population, relative to the early Xight P. canadensis (Table 1). In contrast, species diagnostic mtDNA RFLPs indicated an absence of P. glaucus-type mtDNA (see "Results") suggesting that the introgression which resulted in recombined Z-chromosomes (Scriber and Ording 2005) likely occurred via introgressed males mating with P. canadensis females.…”
Section: Discussionmentioning
confidence: 98%
“…Females of both early Xight and late Xight populations were allowed to oviposit either inside nylon screen sleeves placed on tree branches or in lab arenas (see Mercader and Scriber 2007;Mercader et al 2009). Resulting larvae were Weld reared on black cherry, Prunus serotina (Rosaceae), in Cambridge, New York and East Lansing, MI, USA.…”
Section: Insect Sourcesmentioning
confidence: 99%
“…2009; Loxdale 2010). Temperature sums for emergence of H. obsoletus differ significantly between host races.…”
Section: Discussionmentioning
confidence: 99%